An Analysis of Graduate Students’ Conceptual Understanding in Heat and Temperature (H&T) Using Three-Tier Diagnostic Test - Moh Irma Sukarelawan; Jumadi Jumadi; Nurulhuda Abdul Rahman (Indonesian Review of Physics (IRiP), 2019)
There have been many studies that investigate H&T misconceptions among students in Indonesia but the respondents are usually limited to senior high school students. This study aims to analyse the conceptual understanding in H&T concepts of Masters of Physics Education students with a focus on identifying their misconceptions. The study employs the survey research design and data were collected using a three-tier diagnostic test. Twelve Masters of Physics Education students who are enrolled in one of the private universities in Yogyakarta City took part in the study. They were selected using the convenient sampling technique. Data on conceptual understanding involve both quantitative and qualitative data. As such, the data was analysed based on the percentage of student response patterns. Results showed that the majority of students (62.5%) have some form of misconceptions about the concepts of H&T and only 22.9% hold the scientifically accepted conceptions. The most common misconception held by the students is that both H&T depend on the material of an object. Other descriptions of conceptual understanding are False Positive (4.2%), False Negative (4.2%), and Lack of Knowledge (6.2%). Interestingly, none of the students made a lucky guess in responding to the test items. We conclude that the pattern in conceptual understanding specifically that of misconceptions are ubiquitous regardless of the level of study. Years of learning have failed to address misconceptions among students even at the graduate level. This result has implications on how learning should be designed to actively resolve the issue of misconceptions among students.